Exploring The Perspectives Of Adolescents In High School In Northern Ghana On Barriers To Accessing Substance Use Services. - Daliri, D.B.; Dei-Asamoa, R.; Abagye, N.; Adjei, D.; Afaya, A.; et al. (Discover Mental Health, 2025)
Background Adolescent substance use is a rising public health concern in Ghana, with limited evidence on youth perspectives regarding service availability and access. Objectives This study explores the adolescents’ perspectives on the barriers to accessing substance use services in Northern Ghana. Design A qualitative exploratory design was employed. Setting This study was conducted in public senior high school in the Bolgatanga Municipality of the Upper East Region of Ghana. Participants Fifteen students aged 12 to 19 years were purposively selected with diversity in age, sex, religion, and residency status. Data collection Data were collected through in-depth interviews and analyzed thematically using Braun and Clarke’s framework. Trustworthiness was ensured through member checking, peer debriefing, and audit trails. Results The study identified several barriers grouped under four themes as follows: stigma, fear and confidentiality concerns, accessibility and affordability challenges, service relevance and adolescent-focused, and peer factors. Conclusion This study found that adolescents in Northern Ghana face significant barriers to substance abuse service use, shaped by four key themes: stigma and confidentiality concerns, accessibility and affordability challenges, lack of adolescent friendly services, and peer influence. These barriers, rooted in systemic, structural, and sociocultural contexts, foster mistrust, limit access, and discourage help-seeking. Addressing them requires adolescent-responsive interventions that prioritize confidentiality, affordability, accessibility, and supportive care aligned with young people’s lived experiences
Research Article
Keywords: Adolescents; Substance use; Service access; Stigma; Qualitative study